1990
DOI: 10.1210/endo-126-3-1780
|View full text |Cite
|
Sign up to set email alerts
|

Neurohypophyseal Hormone Regulation of Endothelin Secretion From Rabbit Endometrial Cells in Primary Culture

Abstract: Immunoreactive endothelin-1 (IR-ET-1) was detected in the cultured medium from endometrial but not myometrial cells of rabbits in primary culture using a specific radioimmuno assay (RIA). Similar results were obtained with a radioreceptor assay using myometrial membranes. In a reverse-phase HPLC synthetic ET-1 and IR-ET-1 of the extract medium from endometrial cells revealed essentially the same elution profiles, as determined by RIA. Two selective agonists of oxytocin (OT) or V1 vasopressin (VP) receptors pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…In addition to its powerful vasoconstrictor actions, ET-1 stimulates the release of prostanoids and endotheliumderived relaxing factor (DeNucci et al, 1988), and is co-mitogenic for vascular smooth muscle cells. The release of immunoreactive ET-1 has recently been described from rabbit endometrial cells in primary culture (Orlando et al, 1990). We have demonstrated the presence of specific binding sites for iodinated ET-1, ET-2 and ET-3 in human uterus (Davenport et al, 1991); this study reports the localization of ET-like immunoreactivity in endometrium and myometrium using immunocytochemistry.…”
Section: Introductionmentioning
confidence: 59%
“…In addition to its powerful vasoconstrictor actions, ET-1 stimulates the release of prostanoids and endotheliumderived relaxing factor (DeNucci et al, 1988), and is co-mitogenic for vascular smooth muscle cells. The release of immunoreactive ET-1 has recently been described from rabbit endometrial cells in primary culture (Orlando et al, 1990). We have demonstrated the presence of specific binding sites for iodinated ET-1, ET-2 and ET-3 in human uterus (Davenport et al, 1991); this study reports the localization of ET-like immunoreactivity in endometrium and myometrium using immunocytochemistry.…”
Section: Introductionmentioning
confidence: 59%
“…Moreover, ET and oxytocin modulate Cai2+ through independent receptors. These findings, and the recent observation that ET is produced by rabbit endometrial cells in culture (25) and is elevated in human amniotic fluid (6), strongly suggest that ET, like oxytocin, is an important endogenous modulator of uterine function.…”
Section: Discussionmentioning
confidence: 78%
“…It was previously shown that human placenta at term contains immunoreactive oxytocin which is released from placental cells under PGF 2a stimulation (39). It was shown in vitro that oxytocin and PGF 2a stimulate secretion of ET-1 from endometrial cells (40), and further hypothesized that placental blood flow is regulated by compartmentalized eicosanoids (41). It is therefore possible that oxytocin and eicosanoids may contribute to regulation of a uterine vasomotor effect (accompanied with elevation of ET-1), which under pathological conditions may lead to hypoxia.…”
Section: Discussionmentioning
confidence: 98%